Ca2+ signaling in arterioles and small arteries of conscious, restrained, optical biosensor mice - Fairfax, Seth T.; Mauban, Joseph R. H.; Hao, Scarlett; Rizzo, Mark A.; Zhang, Jin; Wier, W. Gil (Frontiers in Physiology, 2014)
Two-photon fluorescence microscopy and conscious, restrained optical biosensor mice were used to study smooth muscle Ca2+ signaling in ear arterioles. Conscious mice were used in order to preserve normal mean arterial blood pressure (MAP) and sympathetic nerve activity (SNA). ExMLCK mice, which express a genetically-encoded smooth muscle-specific FRET-based Ca2+ indicator, were equipped with blood pressure telemetry and immobilized for imaging. MAP was 101±4 mmHg in conscious restrained mice, similar to the freely mobile state (107±3 mmHg). Oscillatory vasomotion or irregular contractions were observed in most arterioles (71%), with the greatest oscillatory frequency observed at 0.25 s-1. In a typical arteriole with an average diameter of ~35 μm, oscillatory vasomotion of a 5-6 μm magnitude was accompanied by nearly uniform [Ca2+] oscillations from ~ 0.1 to 0.5 μM, with maximum [Ca2+] occurring immediately before the rapid decrease in diameter. Very rapid, spatially uniform ‘Ca2+ flashes’ were also observed but not asynchronous propagating Ca2+ waves. In contrast, vasomotion and dynamic Ca2+ signals were rarely observed in ear arterioles of anesthetized exMLCK biosensor mice. Hexamethonium (30 μg/g BW, i.p.) caused a fall in MAP to 74±4 mmHg, arteriolar vasodilation, and abolition of vasomotion and synchronous Ca2+ transients. Summary. MAP and heart rate were normal during high-resolution Ca2+ imaging of conscious, restrained mice. SNA induced continuous vasomotion and irregular vasoconstrictions via spatially uniform Ca2+ signaling within the arterial wall. FRET-based biosensor mice and two-photon imaging provided the first measurements of [Ca2+] in vascular smooth muscle cells in arterioles of conscious animals.